Choosing interventions for hip or knee osteoarthritis - What matters to stakeholders? A mixed-methods study. Issue 3 (September 2020) - Chua, Jason; Briggs, Andrew M.; Hansen, Paul; Chapple, Cathy; Abbott, J. Haxby
Summary: Objective: To identify what factors drive choices among interventions for hip or knee osteoarthritis (OA), and to rank the characteristics of interventions. Methods: In this phased, mixed-methods design involving cross-sectoral and multi-disciplinary stakeholders – healthcare consumers, providers, policy-makers, Māori health advocates and OA experts – we used the Nominal Group Technique in focus groups to generate data. We conducted thematic analysis of the focus group data to inform a framework of categories and sub-categories describing factors and characteristics influencing the choice of OA interventions. We then used a dual-panel, two-round e− Delphi survey to verify the framework and rank the characteristics of interventions. Results: From six focus groups (n = 38 participants), 364 factors were identified and clustered into 56 themes (mean 9 themes per focus group; range 5–15). Thematic analysis revealed a framework of 3 core categories: characteristics of interventions (10 sub-categories), characteristics of consumers (10 sub-categories) and characteristics of the health system (7 sub-categories). In Delphi round 1, the framework was verified by each of two panels (n = 65, ≥80% acceptability). In round 2, two characteristics of interventions were combined, resulting in 9 characteristics (in decreasing order of importance): effectiveness, appropriateness, quality of the evidence, accessibility, harm, cost, duration, passivity, and immediacy of intervention effect. Conclusion: Stakeholders make choices among interventions for hip or knee OA within a framework of characteristics of interventions, of consumers, and of the health system. We identified and ranked 9 key characteristics of interventions that stakeholders consider when choosing or recommending interventions for hip or knee OA.